Evaluation of Animal Dungs as Alternative Heat-Treating Materials in Foundry Shop - ADETONA, Enoch; ABUBAKRE, Oladiran K.; MURIANA, Rasheed A.; BALA, Muhammad N.; ADEYI, Abel A. (FUDMA Journal of Engineering and Technology, 2026)
The use of steel in engineering materials is diverse due to its adjustable properties heavily relying on heat treatment process. Properties to fit design purposes and to provide desirable mechanical properties combinations such as ductility, toughness, and hardness are possibilities. The mechanical properties of samples of medium carbon steel are examined after heat treatment using animal dungs as cooling/quenching media. These steel samples were heated at 950°C (above critical temperature, quenching) and soaked for 10 minutes in muffle furnace before cooling in respective media (Cow, Donkey and Horse Dung). The mechanical behaviour of the sample was investigated using Monosanto tensile testing machine for tensile and comprehensive tests and Brinell hardening method for hardness test. The microstructure of these samples was examined using SEM (Scanning Electron Microscope). The experimental result showed that sample heat treated with cow dung have highest ultimate tensile strength, comprehensive and hardness value of 866 MPa, 945.33 MPa and 208 BHN, respectively. Hence, waste cow dung can be used as a potential low-cost heat-treating material in a foundry.